ANALISIS PENGARUH FRAUD PENTAGON DALAM MENDETEKSI FRAUDULENT FINANCIAL REPORTING PADA PERUSAHAAN JASA NONKEUANGAN - Yuliamos Tirta Wijaya Pasaribu; Synthia Madya Kusumawati; L. Jade Faliany (Universitas Multimedia Nusantara, 2020)
Abstract– This research aimed at analyzing the effect of fraud pentagon proxied by nine variables, namely financial stability, personal financial needs, external pressure, financial targets, ineffective monitoring, industry characteristics, auditor changes, director changes, and frequent number of CEO’s picture towards fraudulent financial reporting proxied by Beneish M-Score at non-financial service companies listed on the Indonesia Stock Exchange (IDX) period 2015-2017. The data used were secondary data obtained from annual reports and financial statements of nonfinancial service companies period 2015-2017 with a total of 285 eligible samples. The data analysis methods used were descriptive statistical analysis and logistic regression analysis. The results showed that the variables of financial stability and the nature of the industry generated a significant and positive effect on fraudulent financial reporting. Meanwhile, the variables of personal financial needs, external pressure, financial targets, ineffective monitoring, auditor changes, director changes, and often the CEO's image were not significant to fraudulent financial reporting. Keywords: Fraud Pentagon, Fradulent Financial Reporting, Beneish M-Score